Kajian Pengembangan Usaha IKM Pangan Komoditas Roti dan Kue di Kota Bogor (Studi Kasus Brownies Elsari, Bogor) - Ade Hendar Purnawan; Wilson H Limbong; Sri Hartoyo (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2012)
This research is aimed to analyze the prospect of small-medium bakery industry, especially that is located in Bogor. The small industries generally still have the same problem when they need credit from the bank for their investment. This research will analyzed these small industries by doing a case study in Elsari Brownies and Bakery Bogor. There are four investment criteria to be calculated or analyzed. They are NPV, IRR, B/C ratio and PBP. The results show that the values of four investment criteria are positive i.e. NPV value and IRR value respectively is Rp113.236.973 and 66.81%, meanwhile B/C ratio value is 1.45 times and Payback Period is 31.69 months. But at normal/liquid condition which there is no wasted product causing by sales return, the analyses result show that to invest in this industry is very reasonable. At that condition the value of NPV is Rp267,157,761, IRR value’s is 132.35%, PBP is 18.4 months and B/C ratio is 2.21 times. As the results of sensitivity analyses, the decreasing of brownies sales factor has significant effect rather than the influence of the increasing of brownies raw materials price factor. But if both factors are happened at the same time, it will cause worst effect than if each factors occurred. The research is also to analyze the problems faced by the Elsari Brownies & Bakery industry. Firstly, the questionnaires are given to Elsari brownies customers. The result shows that 60% of respondents feel to be satisfied enough with this product (Elsari brownies) and 36% of respondents are satisfied with this product. 74% of respondents said that the brownies price is cheap enough and 50% of respondents say that this product is delicious enough. Finally, the SWOT analyzed is to be done. The Internal-External Matrix shows that this industry is in fifth cell. The result recommends the Elsari industry to do the hold and maintain strategy. The appropriate strategies for fifth cell are market penetration and product development. Elsari should do the following strategy for market penetration: widening market network into well known-food restaurant and tourism places that located at outside Bogor as marketing main target, by making relationship with existing counters at those places or build a new branch. The appropriate strategy for product development is making more ‘broker’ product.  Key words: investment criteria, sensitivity analyses, strategy